The Escherichia coli replication inhibitor CspD is subject to growth‐regulated degradation by the Lon protease - Langklotz, Sina; Narberhaus, Franz (Molecular microbiology, 2011)
Summary Post‐translational proteolysis‐dependent regulation of critical cellular processes is a common feature in bacteria. The Escherichia coli Lon protease is involved in the control of the SOS response, acid tolerance and nutritional deprivation. Moreover, Lon plays a role in the regulation of toxin–antitoxin (TA) systems and thereby is linked to persister cell induction. Persister cells represent a small subpopulation that has reversibly switched to a dormant and non‐dividing state without genomic alterations. Formation of persister cells permits viability upon nutritional depletion and severe environmental stresses. CspD is a replication inhibitor, which is induced in stationary phase or upon carbon starvation and increases the production of persister cells. It has remained unknown how CspD activity is counteracted when growth is resumed. Here we report that CspD is subject to proteolysis by the Lon protease both in vivo and in vitro. Turnover of CspD by Lon is strictly adjusted to the growth rate and growth phase of E. coli, reflecting the necessity to control CspD levels according to the physiological conditions.